Un articolo inedito di André Robinet: Le modele cybernétique dans la pensée politico-technique de G. W. Leibniz - Antonio Lamarra (Lexicon Philosophicum)
An unpublished paper by André Robinet, which is dated February 5th, 2005 and focuses on Leibniz’s theory of law and justice, is edited and introduced by some preliminary remarks and clarifications. An explanation is proposed concerning Robinet’s claim according to which Leibniz’s use of the French noun ‘gubernation’ justifies speaking of a cybernetic model in his political and law philosophy. His 1994 book on Leibniz’s political thought, which is presupposed, has been consulted to clarify some aspects of Robinet’s article, which is devoid of footnotes. Some of the main texts by Leibniz on the subject have been identified, which are underlying in Robinet’s article.